Nutritional Quality of Bivalves, Crassostrea madrasensis and Perna viridis in the Kali Estuary, Karnataka, India - V.N. Nayak, G.M. Salaskar and (Recent Research in Science and Technology, 2011)
Quality aspects of oysters (Crassostrea madrasensis) and mussel (Perna viridis) in the Kali estuary, Karwar were examined in different seasons over a 13 month period. Ecophysiological parameters and nutritional quality parameters of oysters and mussel (composition of Protein, Carbohydrate, Lipid and Ash content) were determined at different seasons of the year. Seasonal variations were observed in the nutrient content, with particular regard to protein 52.33% (September 2003) to 63.86% (June 2004); Carbohydrate 14.01% (February 2004) to 25.24% (October 2003), Lipid 8.46% (October 2003) to 18.77% (February 2004) ash 4.21% (February 2004) to 14.82% (September 2004) in oysters whereas in mussels protein 57.39%Ã‚Â (March 2004) to 66.51% (November 2003), Carbohydrate 14.69% (November 2003) to 26.81% (March 2004), Lipid 8.09% (Feb. 2004) to 12.62% (November 2003), ash 6.18% (November 2003) to 9.02% (March 2004). In spite of this variability, the nutritional quality of the oysters was generally good, especially just before gamete release (premonsoon) when the concentration of nutrients was at its maximum. A low level of fat was detected in the edible meat of oysters and mussels.